2008
DOI: 10.1111/j.1945-5100.2008.tb00650.x
|View full text |Cite
|
Sign up to set email alerts
|

The loss of K, REE, Th, and U from a Martian and a terrestrial basalt by acidic leaching

Abstract: Abstract-The mobilization of K, rare earth elements (REE), Th, and U from Martian surface material upon contact with acidic solutions probably occurred extensively on Mars about 4 to 3.5 Ga ago and seems to have occurred locally in more recent times. We have studied the dissolution of these elements by leaching the basaltic shergottite Zagami and the terrestrial basalt BE-N at constant pH values ranging from 5 to 1 in the absence and presence of added salts. Potassium is nearly immobile in Zagami and mobilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The surface and crust of Mars have been the focus of intensive study by orbital spectroscopic observations and in situ surface analysis by landers and rovers [e.g., Bibring et al ., , ; Carr , ; Christensen et al ., ; Ehlmann et al ., ; Grotzinger and Milliken , ; McEwen et al ., ; McLennan et al ., ; McSween et al ., , ; Murchie et al ., ; Poulet et al ., ; Squyres et al ., ; Stolper et al ., ]. Additionally, there have been many detailed analytical investigations of Martian meteorites [e.g., Borg and Draper , ; Brandon et al ., ; Day et al ., ; Dyar et al ., ; Greenwood et al ., ; Herd et al ., ; McCubbin et al ., ; McKay et al ., ; McSween and Treiman , ; Monkawa et 9al ., ; Nyquist et al ., ; Papike et al ., ; Sarbadhikari et al ., ; Shearer et al ., ; Steele et al ., ; Treiman , ; Usui et al ., ; Wadhwa , ] as well as experimental studies that have simulated Martian conditions in the laboratory [e.g., Adcock et al ., ; Collinet et al ., ; Dreibus et al ., ; Filiberto , ; Filiberto and Dasgupta , ; Filiberto et al ., , ; Golden et al ., ; Hurowitz et al ., ; McCanta et al ., ; McCubbin et al ., ; McSween et al ., ; Medard and Grove , ; Monders et al ., ; Musselwhite et al ., ; Nekvasil et al ., ; Papike et al ., ]. These studies have shown that the planet Mars has had a complex geologic history.…”
Section: Introductionmentioning
confidence: 98%
“…The surface and crust of Mars have been the focus of intensive study by orbital spectroscopic observations and in situ surface analysis by landers and rovers [e.g., Bibring et al ., , ; Carr , ; Christensen et al ., ; Ehlmann et al ., ; Grotzinger and Milliken , ; McEwen et al ., ; McLennan et al ., ; McSween et al ., , ; Murchie et al ., ; Poulet et al ., ; Squyres et al ., ; Stolper et al ., ]. Additionally, there have been many detailed analytical investigations of Martian meteorites [e.g., Borg and Draper , ; Brandon et al ., ; Day et al ., ; Dyar et al ., ; Greenwood et al ., ; Herd et al ., ; McCubbin et al ., ; McKay et al ., ; McSween and Treiman , ; Monkawa et 9al ., ; Nyquist et al ., ; Papike et al ., ; Sarbadhikari et al ., ; Shearer et al ., ; Steele et al ., ; Treiman , ; Usui et al ., ; Wadhwa , ] as well as experimental studies that have simulated Martian conditions in the laboratory [e.g., Adcock et al ., ; Collinet et al ., ; Dreibus et al ., ; Filiberto , ; Filiberto and Dasgupta , ; Filiberto et al ., , ; Golden et al ., ; Hurowitz et al ., ; McCanta et al ., ; McCubbin et al ., ; McSween et al ., ; Medard and Grove , ; Monders et al ., ; Musselwhite et al ., ; Nekvasil et al ., ; Papike et al ., ]. These studies have shown that the planet Mars has had a complex geologic history.…”
Section: Introductionmentioning
confidence: 98%
“…Leaching, the chemical alteration or chemical weathering of minerals by selective dissolution of elements, has long played a significant role in pedogenesis-the evolution of martian soils (Dreibus et al, 2008;Hurowitz et al, 2006;Retallack, 2014;Thorpe et al, 2021Thorpe et al, , 2022Ye & Michalski, 2021). Of special importance to near-surface processes on Mars, leaching generates fluids rich in elements that can then migrate and participate in authigenic and diagenetic mineralization over a wide range of temperatures (Bullock & Moore, 2004).…”
Section: Leachingmentioning
confidence: 99%